Dosimetric comparison of whole pelvic radiotherapy for post-operative endometrial cancer using three-dimensional conformal radiotherapy and intensity-modulated radiotherapy technique - Anand RK; Praveen J Ninan; Haritha VS (Asian Journal of Medical Sciences, 2025)
Background: The use of intensity-modulated radiation technique is being used increasingly in gynecological patients. It plays an important role in the adjuvant treatment of gynecologic malignancies, particularly in cervical and endometrial cancer. While radiotherapy (RT) has greatly improved local-regional control of primary tumors, it has come at the cost of significant toxic effects on adjacent non-cancerous tissues. Aims and Objectives: The purpose of this study was to perform a direct dosimetric comparison between the three-dimensional radiation technique and intensity modulation radiation technique in post-operative endometrial cancer patients and to evaluate the integral dose to organs at risk (OAR). Materials and Methods: We selected 49 patients with endometrial cancer undergoing post-operative whole pelvic RT. Plans for three-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy (IMRT) were developed for each patient. All plans were normalized to deliver 45 Gy to 95% of the planning target volume. The dosimetry and integral dose to OARs were compared. The significance of differences was tested using a paired Student t-test. Results: IMRT had significantly better conformity and reduced mean dose and integral dose to OARs in comparison to 3D-CRT. Conclusion: In post-operative endometrial cancer patients IMRT had better dose conformity and reduced integral and mean dose to OARs when compared to 3D-CRT. The clinical significance of these dosimetric differences needs to be further investigated.